Driver Configurations for Successful Service Infusion. (August 2017) - Forkmann, Sebastian; Henneberg, Stephan C.; Witell, Lars; Kindström, Daniel
Manufacturers across many industries use service infusion to address the changing customer demands and improve their competitive position. However, understanding the drivers of successful service infusion is a complex process. Using business model and configuration theories, this study conceptualizes and analyzes the interplay of different driver domains for suppliers, customers, and their business relationships. In particular, we analyze how service offering, service pricing, service capabilities, and the service infusion process interact in affecting service infusion success and failure. 137 interviews relating to 25 business relationships are analyzed via configuration analysis, particularly fuzzy set qualitative comparative analysis (fsQCA). Results show that different equifinal configurations exist (i.e., different ways to succeed with service infusion). We also find that "more is not always better." For example, service infusion success can be achieved without fully developed service capabilities. In addition, successful configurations are often very similar to those leading to failure. A dyadic analysis demonstrates that customer service capabilities are overall more important than those of suppliers. From these findings, we derive priorities for future research. In particular, our study points toward the need to better understand the interplay between service infusion drivers. Second, we advocate the augmentation of research perspectives in service infusion by taking into account the supplier, customer, and dyadic perspectives. Lastly, the importance of understanding drivers of service infusion failure is highlighted. For managers, our study shows the importance of relational audits as a starting point to deciding on how to infuse services in a business relationship.